STRATEGI PENGEMBANGAN DESA WISATA DALAM MENINGKATKAN DAYA TARIK WISATAWAN PADA WISATA SAWAH DI DESA BAJANG KECAMATAN PAKONG KABUPATEN PAMEKASAN - Jufri, Ahmad; Romli, Mohammad Saedy; Nazizah, Fitrotin (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2023)
The tourism industry is one of the country's sources of foreign exchange and its development isexpected to encourage national economic growth. This research aims to determine the potential forrice field tourism and strategies for developing tourist villages in increasing tourist attraction for ricefield tourism in Bajang Village, Pakong District, Pamekasan Regency. The research method usesqualitative descriptive analysis and sampling using the Purposive Sampling method because theresearch informants were determined deliberately. The data analysis method uses the SWOTanalysis method to determine the strategy for developing rice field tourism. The results of thisresearch indicate that the appropriate strategy for developing Rice Field Tourism is the SO Strategy,namely adding contemporary facilities by combining agricultural concepts such as buildingagrotourism facilities, agricultural themed cafes or restaurants and agricultural-based recreationfacilities, creating agricultural-based events, publishing on social media.